If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64y = 7(9y + -3) Reorder the terms: 64y = 7(-3 + 9y) 64y = (-3 * 7 + 9y * 7) 64y = (-21 + 63y) Solving 64y = -21 + 63y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-63y' to each side of the equation. 64y + -63y = -21 + 63y + -63y Combine like terms: 64y + -63y = 1y 1y = -21 + 63y + -63y Combine like terms: 63y + -63y = 0 1y = -21 + 0 1y = -21 Divide each side by '1'. y = -21 Simplifying y = -21
| 53=x-5x+9 | | 33-[3+6y-4(y+3)]=-4(5y-5)-[5(y-1)-19y+11] | | 5x-4y=24 | | 15q-17=13 | | 3n-1=-61 | | 5x-4(0)=24 | | 4x-7=1x+5 | | -3y+9=19y-2 | | 4n=-8 | | 5(2c-1)-4=7c+6 | | 53=x-5x-9 | | 2x^3-3x^2-23x+12=0 | | 14*8= | | 2.5*2.5= | | 3-7x=12+2x | | -176=16x | | 6x-8=7x+6 | | 4(x-3)+16=3(x+4) | | Z-8=-12 | | -9-5m=2m+5 | | 6x-8x=7x+6 | | 0=x^3-3x^2+3x-1001 | | X+1=x+2 | | 21x-7=5+17x | | 4y-8=10y+28 | | -10p+425=0 | | -(-3)+7-6(-3)=19-3(-3) | | 14x-5=5x+12x | | 5x^2+20x+15=0 | | 5x+18=-4c | | y+7*4=10 | | y+7*0=10 |